Image privacy preservation scheme based on QR code and reversible visible watermarking - Yuanzhi YAO; Feng WANG; Wenbo YAN; Nenghai YU (Tongxin xuebao)
With the privacy leakage problem of image delivery in networks,an image privacy preservation scheme based on QR code and reversible visible watermarking was proposed.In order to preserve the privacy information including shooting time,shooting location and detailed description,the encrypted privacy information was stored in cloud platforms and corresponding universal resource locator was generated firstly.Secondly,the universal resource locator was encoded as the QR code and it was embedded into the cover image using reversible visible watermarking.Therefore,the access control for privacy information could be achieved.The visual perceptual model was utilized to select adaptive watermark embedding parameters to balance watermark visibility and marked image quality.Experimental results demonstrate that the good visual quality of marked images can be obtained and the embedded QR code can be correctly decoded.The proposed scheme can guarantee marked image quality and reduce the risk of private information leakage.